Lectotype designations and new synonymies in the Neotropical bee genus Centris Fabricius, 1804 (Hymenoptera: Apidae) - Rasmussen, Claus; Vivallo, Felipe (Zootaxa, 2014)
Ten name-bearing specimens of Centris Fabricius deposited in the Hungarian Natural History Museum are examined and nine lectotypes are designated for the following species: C. atripes Mocsáry, 1899; C. flavilabris boliviensis Mocsáry, 1899; C. facialis Mocsáry, 1899; C. fusciventris Mocsáry, 1899; C. mariae Mocsáry, 1896; C. minuta Mocsáry, 1899; C. obsoleta pleuralis Friese, 1901; C. proxima Friese, 1899, and C. vidua Mocsáry, 1899. Two names are newly established as synonyms: C. nitida geminata Cockerell, 1914 syn. nov. = C. facialis Mocsáry, 1899; C. pleuralis Friese, 1901 syn. nov. = C. obsoleta Lepeletier de Saint Fargeau, 1841. Comments on the repository of the holotype of C. horvathi Friese are also provided.